Vehicle scheduling with heterogeneous bus fleet - Palúch, Stanislav; Peško, Štefan (Univerzita Pardubice, 2010)
The paper studies vehicle scheduling problem formulated as to minimize the number of vehicles with several types of buses. A general mathematical model is presented using graph coloring and bivalent linear programming formulation. A suboptimal algorithm is designed and the way is proposed how to exploit its result to reduce the corresponding bivalent linear programming model.
Keywords: vehicle scheduling; heterogeneous bus fleet